ANALISIS IKLAN SIMPATI DENGAN MENGGUNAKAN CONSUMER DECISION MODEL - Reni Shinta Dewi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2009)
In order that position of a brand always engage in the mind of consumers, the company does not only act positioning strategy, but they have to give the right information about their product, and advertising on the television is one of the most effective promotion media. The main reaction of advertisement is purchase, but it’s happened in the end of the long process before the consumer makes their decision. Usually the effect of advertising communication is to measure the awareness, knowledge, preference and confidence. One of model can be used to measure the advertising effectiveness is Consumer Decision Model (CMD) by Howard, Shay and Green. The findings indicated that information, brand recognition, attitude, and confidence are identified as intervening variable which can strongly effect information to customer’s intention. Structural analysis seen that the biggest influence to intention shown by variable of advertisement message through attitude and confidence. The ability of advertisement to create attitude and confidence which supporting a product oftentimes hinging to consumer’s attitude and confidence to advertisement itself. The advertisement which evaluated better can yield positive attitude to product. Even sometimes, that unwelcome advertisement can succeed. This matter happens because the advertisement schema is salience in consumer’s view. The fact said that attitude developed by brand is more difficult than customer’s confidence. To create consumer’s attitude which is direct to consumer’s intention, continuity and intensity of commercials are recommended.